Periungual Pyogenic Granuloma: The Importance of the Medical History - Alessandrini, Aurora (Skin Appendage Disord, 2016)
Pyogenic granuloma (PG) is a common, benign vascular proliferation that can arise on the skin or subcutaneous tissue. It is more frequent in the early decades of life, and the most common locations are the digits of both hands and feet. The most common cause of periungual PG is drug intake, but many other trigger factors have been described in the literature. Treatment should be chosen according to the cause. We describe 2 particular cases of periungual PG in which the clinical history has been fundamental. In the first case, there was an underlying hand eczema, and in the second case, a foreign body was present.